European experience of the local budgets formation - KANIEVA, Тетяна; DREPIN, Антон (Ius Modernum, 2019)
Background. In the context of improving the domestic fiscal system, it is expedient to systematize, analyze and adapt foreign experience to improve the efficiency of local budgets and provide economic growth on this basis. The processes of decentralization in view of its many years of experience in implementing it deserve attention, in particular the quality of institutional support for resource-sharing processes, which affects the result of social production. The aim of the article is to systematize approaches to the formation of local budgets in European countries, taking into account the peculiarities of socio-economic development and the configuration of the model of inter-budgetary relations. Materials and methods. Theoretical and methodological basis of work is the scientific works on selected topics. Its character has necessitated application of specific and general scientific methods, in particular: a system approach, comparative and statistical analysis, synthesis, generalization and systematization, scientific abstractions. Results. The experience of forming local budgets in the countries of Europe with developed and transformational economies has been systematized and generalized. The state of decentralization of its budgetary systems by expenditures and incomes is investigated in view of the achieved level of economic development. The role of innovative financial practices, in particular, the formation of budgets of participation and the program-target method at the level of administrative-territorial units has been characterized. Conclusion. The systematization and use of foreign experience in the formation of local budgets, taking into account national specifics, ensures its effectiveness. Fiscal decentralization with rational constraints contributes to the growth of the quality of public services. In Europe, the development of the local budget project is carried out with the orientation of the costs for the result and the strengthening of its productive component, the consolidation of the connection of operational and long-term planning. Budget policy is characterized by innovative methods: private-public partnership, participation of the territorial community, general quality management, budgeting with zero bases, program-target method.